Investigating a Foodborne Outbreak at A Nationwide School Event in Northeast Malaysia - Bin Sha’Ari, Ahmad Zulfahmi; bin Khalid, Mohd Khairul Ashraf; Mohd Kamaruzaman, Ahmad Zulfahmi Bin; Wan Mohd Hanafi, Wan Soliha Binti; Dir, Sharina Binti (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Investigating complex food and waterborne outbreaks poses challenges due to diverse pathogens and symptoms. Objectives: This study focused on a foodborne outbreak during a nationallevel event in Kota Bharu, Malaysia, which aimed to describe the outbreak, identify risk factors, locate the source, and detail control measures. Methods: Active and passive methods, interviews, record reviews, lab tests, and environmental assessments were used. A case-control study defined cases as individuals experiencing abdominal pain, diarrhoea, dizziness, nausea, and vomiting. They were compared with a 1:2 asymptomatic control group. Demographic and food history data were collected through an online form distributed to related health district offices, involving 81 boarding schools across the country and international counterparts from Indonesia, Thailand, and China. Statistical analysis was performed using Microsoft Excel 365 and Hazard Analysis and Critical Control Point (HACCP) application. Results: Among 941 exposed individuals, 126 cases (attack rate:13.8%) occurred. Common symptoms included abdominal pain(84%), nausea(51%), diarrhoea(44%), dizziness(44%), and vomiting(44%). The epidemiological curve indicated a point source pattern, with a 1-to-20-hour incubation period. Causative foods were white rice (OR:8.2, 95% CI:3.66,18.37) and chicken with paprika sauce (OR:8.5, 95% CI:3.80,19.03), both statistically significant (p<0.001). HACCP analysis identified food handling issues, with Bacillus cereus isolated from food handlers. To mitigate the situation, premises were temporarily closed, and a health education program was conducted. Conclusion: This study underscored the significance of digital tools and food safety protocols in tracing foodborne outbreak origins. These are crucial for safeguarding public health and averting future incidents. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 207-211